Study protocol of a randomized controlled trial for the synergizing effects of rTMS and Tui Na on upper limb motor function and cortical activity in ischemic stroke - Chen, Yu-Feng; Zhu, Guang-Yue; Mao, Meng-Chai; Zheng, Ya; Huang, Hao; Liu, Lan-Lan; Chen, Si-Yun; Cao, Ling-Yun; Xu, Dong-Sheng (Frontiers in Neurology, 2022)
Upper limb motor dysfunction after stroke is a serious threat to the living quality of patients and their families. Recovery of upper limb motor function after stroke largely relies on the activation and remodeling of neural circuits. rTMS (repetitive transcranial magnetic stimulation) has been proved to promote the reconstruction of neural synapses and neural circuits. However, there are still a large number of patients who can not fully recover and leave behind varying degrees of dysfunction. Considering the systemic pathology after stroke, in addition to focal brain injury, stroke can also cause extensive dysfunction of peripheral organs. The rehabilitation strategy for stroke should combine the treatment of primary brain lesions with the intervention of secondary systemic damage. The aim of this trial is to verify the efficacy of rTMS synergize with Tui Na (Chinese Massage) on upper limb motor function after ischemic stroke, and to explore the mechanism of activation and remodeling of sensorimotor neural circuits with functional near-infrared spectroscopy. Ninety patients will be randomly assigned to either rTMS + Tui Na + conventional rehabilitation group (the experimental group) or rTMS + conventional rehabilitation group (the control group) in 1:1 ratio. Intervention is conducted five sessions a week, with a total of twenty sessions. The primary outcome is Fugl-Meyer Assessment, and the secondary outcomes include Muscle Strength, Modified Ashworth Assessment, Modified Barthel Index Assessment, motor evoked potentials and functional near-infrared spectroscopy. There are four time points for the evaluation, including baseline, 2 weeks and 4 weeks after the start of treatment, and 4 weeks after the end of treatment. This study is a randomized controlled trial. This study was approved by Institutional Ethics Committee of Shanghai Third Rehabilitation Hospital Affiliated to Shanghai University of Traditional Chinese Medicine (approval No. SH3RH-2021-EC-012) on December, 16th, 2021. The protocol is registered with Chinese Clinical Trial Registry (ChiCTR2200056266), on February 3th, 2022. Patient recruitment was initiated on February 10th, 2022, and the study will be continued until December 2022.